Balancing bioenergy and biosecurity policies: estimating current and future climate suitability patterns for a bioenergy crop. Issue 5 (9th April 2013) - Kriticos, D. J.; Murphy, H. T.; Jovanovic, T.; Taylor, J.; Herr, A.; Raison, J.; O'Connell, D.
Abstract In an apparent paradox, bioenergy crops offer potential benefits to a world adjusting to the challenges of climate change and declining fossil fuel stocks, as well as potential ecological and economic threats resulting from biological invasions. In considering this paradox it is important to understand that benefits and threats may not always be apparent in equal measure throughout the potential range of each candidate biofuel species. In some environments, a species could potentially produce valuable biological materials without posing a significant invasion threat. In this study, we develop a bioclimatic niche model for a candidate biofuel crop, Millettia pinnata, and apply the model to different climatic and irrigation scenarios to estimate the current and future patterns of climate suitability for its growth and naturalization. We use Australia as a case study for interpreting the niche model in terms that may be informative for both biofuels proponents and biosecurity regulators to plan management programmes that reflect the invasive potential in different areas. The model suggests that suitable growing conditions for M. pinnata in Australia are naturally restricted to the moist and semimoist tropics. Irrigation can extend the suitable growing conditions more widely throughout the tropics, and into more arid regions. Under future climate scenarios, suitable growing conditions for M. pinnata under natural rainfall contract towards the east coast, and extend southward into the subtropics. With irrigation, M. pinnata appears to have the potential in the future to naturalize across much of Australia. The bioclimatic modelling method demonstrated here is comparatively quick and easy, and can produce a rich array of data products to inform the interests of both bioenergy proponents and biosecurity regulators. We show how this modelling can support the development of spatially explicit biosecurity policies designed to manage invasion risks in a manner that balances bioenergy and biosecurity concerns.